Cultural Keystone Places and Historical Ecology: Conceptual Benefits and Ethical Impacts - Wolverton, Steve; Armstrong, Chelsey Geralda (Ethnobiology Letters, 2025)
The papers in this special issue employ cultural keystone places (CKPs) as a concept to engage scholarship about land. The CKP concept is used in contrast to Eurocentric understandings of place and instead acknowledges the deeper meanings of place to local communities. Research employing the concept is increasingly common through the lens of historical ecology, an integrative research paradigm in ethnobiology and archaeology. In this introduction we articulate what the CKP concept has to offer ethnobiology and archaeology, particularly in terms or practices of ethical inquiry about research, which we term ethical sufficiency. Addressing ethical sufficiency of research also requires addressing the limitations of and challenges to disciplines and academic communities steeped in settler-colonial histories.